Gender Inequality and Power Imbalance in Taylor Swift’s Songs “Dear John” and “All Too Well” - Imtiyaz, Rana; Ramadhina, Retno; Priyoto, priyoto (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This study looks at how gender inequality and power imbalances in romantic relationships are shown in Taylor Swift's songs "Dear John" and "All Too Well." This research uses two theories, Raewyn Connell's Theory of Hegemonic Masculinity and Sylvia Walby's Theory of Patriarchy, to analyze the lyrics of these songs. The findings show how traditional ideas of masculinity, like emotional detachment and control, can lead to unfair relationships. The analysis also shows how patriarchy works, including emotional manipulation, male violence (both emotional and psychological), and the cultural acceptance of male dominance. These ideas are shown in the songs' narratives. The conclusion shows how Swift's lyrics strongly comment on the common issues of gender inequality and power imbalance in personal relationships. They challenge traditional ideas of male power and express the experience of women in these situations